Revolutionizing Ripple Tank Experiments: Innovative Tools to Enhance the Wave Phenomena and Characteristics Learning - Md Hairi, Muhammad Fauzi; Yap Wing Fen; Khairul Adib Yusof; Ismail, Muhammad Faiz Iqbal; Samuri, Muhammad Nazreen; Kamarudin, Nurzatulshima; Khusaini, Khusaini (Jurnal Pendidikan Fisika Indonesia, 2025)
The ripple tank is one of the important experimental tools for teachers and students in the teaching and learning of wave physics. It is necessary for teachers to demonstrate various phenomena related to water waves for better students' understanding. However, it is often less ideal to carry out the experiment using a conventional setup outside the laboratory setting due to its lack of portability. This study develops a portable ripple tank to enhance the teaching experience in wave phenomena and characteristics. Traditional ripple tanks face limitations in terms of size, portability, and observation clarity, prompting the need for innovation. The proposed portable ripple tank addresses these challenges by integrating low-cost materials and electronic components to improve accessibility and functionality. This study aimed to design and evaluate a portable ripple tank integrated with digital components to enhance classroom usability and learning outcomes. Through the adoption of the ADDIE instructional design model, the study systematically analyzes the needs of 20 physics teachers through semi-structured interviews and direct observations, which enables the key issues with existing ripple tanks in school laboratories to be identified. Subsequently, the portable ripple tank was designed and developed, incorporating features such as a digital stroboscope and an alternative power supply for enhanced usability. In the implementation, five-wave experiments were conducted using the tool to evaluate its effectiveness in teaching key wave concepts such as reflection, refraction, diffraction, and interference. In evaluation phases, the effectiveness of the portable ripple tank is assessed by three expert teachers, who assess the tool’s usability and effectiveness in classroom settings, confirming its practicality, affordability, and impact on students’ understanding. This research contributes to the advancement of wave physics education by providing educators with a versatile and user-friendly experimental tool, enabling students to visualize and understand complex wave concepts with ease.